Model of Level Preparation of Primary School Teachers to Conducting Pedagogical Researches - Oksana Shkvyr (Pedagogical Discourse, 2017)
The article focuses on the problem of level preparation of future primary school teachers to conducting pedagogical researches. It is noted that the question of grounding the conceptual foundations of the level preparation of the future teachers to conducting pedagogical researches requires deeper investigation. The essence of the concept «model of level preparation of the future teachers to conducting pedagogical researches» has been cleared out. We understand it as a set of interrelated elements of the pedagogical process at each level of higher education, which provides gradual development of students’ research qualities, scientific thinking and mastery of research knowledge and skills. The author’s model of the mentioned preparation has been offered. The attention is focused on the main components of the model: general goal, tasks of each phase and the results of preparation. The key approaches and principles of preparation of the future primary school teachers to conducting pedagogical researches have been mentioned. The structure of the system of preparation, which includes three components: value-motivational, cognitive, operational-active has been revealed. Value-motivational component provides for the formation of valuable attitude to pedagogical activity in general and to the research one as its leading function; developing of students’ positive motivation. The cognitive component involves the formation of the system of research knowledge, specifying the nature and the content of the research activity of the primary school teacher in accordance with the specifics of its implementation and development of pedagogical thinking of the future teacher, since the research activity sets special demands to the cognitive actions of the pedagogue. The basis of the operational-active component is teaching students research actions, improving the methods of conducting pedagogical researches, developing research skills and pedagogical experience. The conclusion about the integrity, phasing and dynamics of the model; the possibility of integrating of the developed system into the existing conditions of higher education has been made. Key words: model of level preparation of the future teachers to conducting pedagogical researches.